Struktur Modal, Ukuran Perusahaan, Pertumbuhan Perusahaan dan Tax Avoidance Terhadap Nilai Perusahaan - Sa'diyah, Chalimatus; Hariyono, Anwar (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This study aims to examine the effect of capital structure, firm size, firm growth and tax avoidance on firm value. The novelty in this study is found in the  population used by manufacturing companies listed on Indonesia Stock Exchange (IDX) during the period 2017-2019. Sample determination was done by purposive sampling method, 168 samples selected on this study. This study uses quantitative methods with secondary data sources in the form of complete company annual reports. Methods of data analysis using multiple linear regression analysis. The results showed that partially the firm size and firm growth have a effect on firm value. While the capital structure and tax avoidance have no effect on firm value. Then, simultaneously the capital structure and firm size have a (significant) effect on firm value. Firm growth and tax avoidance have a effect on firm value.